2017
DOI: 10.1002/ijgo.12284
|View full text |Cite
|
Sign up to set email alerts
|

Radical hysterectomy after radiotherapy for recurrent or persistent cervical cancer

Abstract: RH-AR was a safe, curative treatment for patients with recurrent or persistent cervical cancer. However, considering the significant risk of surgical adverse events, RH-AR should only be performed for a select group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…In comparison, in our study, 63.8% of patients received a combination of external beam radiation plus additional brachytherapy. In a study by Mabuchi et al, 8 of 30 (27%) patients who received radical hysterectomy after pelvic external beam irradiation with brachytherapy experienced severe postoperative adverse events, such as ureteral stenosis, ureteral perforation, infected lymphocele, and fistula formation . Kaidar‐Person et al did not report any treatment complications in their series.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In comparison, in our study, 63.8% of patients received a combination of external beam radiation plus additional brachytherapy. In a study by Mabuchi et al, 8 of 30 (27%) patients who received radical hysterectomy after pelvic external beam irradiation with brachytherapy experienced severe postoperative adverse events, such as ureteral stenosis, ureteral perforation, infected lymphocele, and fistula formation . Kaidar‐Person et al did not report any treatment complications in their series.…”
Section: Discussionmentioning
confidence: 96%
“…13,26,27 In comparison, in our study, 63.8% of patients received a combination of external beam radiation plus additional brachytherapy. In a study by Mabuchi et al, 28 18 reported that cumulative incidence of severe late morbidity at 2 and 5 years after treatment was higher in patients receiving additional radical hysterectomy than in patients not receiving surgery (16.2% vs 4.3% at 2 years and 22.5% vs 6.5% at 5 years). However, they also noted that severe morbidity was lower in patients who had laparoscopic surgery than in patients who underwent laparotomy (6.7% vs 20.5%).…”
Section: Discussionmentioning
confidence: 98%
“…Radiotherapy or CCRT is the standard treatment for central or lateral pelvic recurrence in patients primarily treated with radical hysterectomy without adjuvant radiotherapy [ 16 , 17 , 18 , 19 , 20 ]. Radical hysterectomy has been seldom used in patients with small (<2 cm) persistent tumor or centrally located recurrence in the cervix or vaginal fornices after definitive radiotherapy [ 16 , 21 , 22 , 23 , 24 ]. This surgical approach obtained 5-year survival rates ranging from 49% to 84%, witha high rate of severe postoperative complications and especially of fistulas.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is employed in treating many advanced gynecological cancers (Yoshida et al, 2016; Mabuchi et al, 2017). Ionizing radiation is delivered around the target site to destroy and prevent recurrence of malignancy (Song et al, 2017).…”
Section: Introductionmentioning
confidence: 99%